Pengaruh Sosialisasi Layanan Mobile Banking dan Persepsi Nasabah Terhadap Kepercayaan Nasabah Bank NTT Cabang Ende - Fransiskus Korosando; Ludvina Fince (Program Studi PGSD Universitas Flores, 2020)
The purpose of this study is to describe (1) the effect of the socialization of the Mobile banking service (m-banking) on ??the trust of Bank NTT Customers in the Ende Branch; (2) the effect of customer perceptions on the trust of NTT Bank Ende Branch Customers; (3) the effect of the socialization of the Mobile banking service (m-banking) and the customer's perception of the trust of the Customers of the NTT Bank Ende Branch. This research is a quantitative study with primary data obtained using a questionnaire technique. Bank NTT Ende Branch customers of the Ende Regency Government ASN profession category as the study population. The research sample uses a simple random sampling technique with accidental sampling approach. The results of the partial test analysis (t test) the effect of sosilaisasi m-banking services on trust shows sig. > 0.05. Partial test (t test) the effect of customer perception on the trust of customers of the Ende Bank NTT branch shows sig. > 0.05. Simultaneous test (f test) of M-banking service socialization, customers' perceptions of the trust of Bank NTT customers in the Ende Branch showed sig> 0.05. The results of the analysis concluded the service socialization variable, and customer perceptions did not significantly influence trust. Thus the hypothesis proposed